Pharmacogenomics in the development and characterization of atheroprotective drugs - Valanti, E.; Tsompanidis, A.; Sanoudou, D. (Methods Mol BiolMethods Mol BiolMethods Mol Biol, 2014)
Atherosclerosis is the main cause of cardiovascular disease (CVD) and can lead to stroke, myocardial infarction, and death. The clinically available atheroprotective drugs aim mainly at reducing the levels of circulating low-density lipoprotein (LDL), increasing high-density lipoprotein (HDL), and attenuating inflammation. However, the cardiovascular risk remains high, along with morbidity, mortality, and incidence of adverse drug events. Pharmacogenomics is increasingly contributing towards the characterization of existing atheroprotective drugs, the evaluation of novel ones, and the identification of promising, unexplored therapeutic targets, at the global molecular pathway level. This chapter presents highlights of pharmacogenomics investigations and discoveries that have contributed towards the elucidation of pharmacological atheroprotection, while opening the way to new therapeutic approaches.
Valanti, EfiTsompanidis, AlexandrosSanoudou, DespinaengResearch Support, Non-U.S. Gov'tReviewClifton, N.J.2014/08/26 06:00Methods Mol Biol. 2014;1175:259-300. doi: 10.1007/978-1-4939-0956-8_11.
Keywords: *Drug Discovery; *Pharmacogenetics; Animals; Atherosclerosis/*drug therapy/epidemiology/*genetics; Fibric Acids/therapeutic use; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors/therapeutic use